Sistem Penunjang Keputusan Penerimaan Staf Pengajar Fakultas Xxx Di Sebuah Universitas Menggunakan Metode Analytical Hierarchy Process - Utama, Ditdit N.; Soenardi, Wenny Asih (Lembaga Penerbitan Universitas Esa Unggul, 2006)
The top leaders of management in one company need accurate decision in some cases. Talk about accurate decision, its talk about right information, effective information, and up to date information. Sometime, top leaders of management face a semi or unstructured problem in their daily activities, so they need the right tools for this situation. Decision Support System can help and support the leaders of company to make decision.Keywords : top leader, Decision Support System, semi structured problem, unstructured problem